Safety : Why Safety Matters for Sustainable Mobility - Job, Soames; Gomez, Hilda (World Bank, Washington, DC, 2018)
Safety is one of four global goals identified in the Global Mobility Report (GMR)—along with universal access, efficiency, and green mobility. The safety goal is aimed at curbing the human pain, suffering, loss, grief, and economic costs of transport-crash-related injuries and deaths. The scale of the safety problem is profound across all transport modes, including air, rail, road, and water. Safety efforts need to be focused on Low- and Middle- Income Countries (LMICs), where 90 percent of the 1.4 million transport crash deaths occur each year. The inclusion of road safety in the Sustainable Development Goal targets has created opportunities for an increased global commitment. Nevertheless, to date there has been no overarching effort to set an overall target for safety of mobility and to collect reliable global data on transport safety across all modes. To increase the momentum, the GMR sets targets for global transport safety aimed at setting a unified transportation safety goal.